A Book I Value - Coleridge, Samuel Taylor,Jackson, H. J. (Princeton University Press, 2003)
Coleridge is such a celebrity that many who have never read
10.1515/9781400825622
Keywords: Aeschylus; Anabaptists; Anaxagoras; Aristophanes; Aristotelean; Barrow; Samuel; Cabbala; Calvinism; Charles I; Creation; Defoe; Daniel; Democritus; Eikon Basilike; Epicurism; Eternal Punishment; Fielding; Henry; Gichtelians; Hades; Hammond; Henry; Heraclitus; Hippocrene; Inquisition; Jacobinism; acoustics; animal magnetism; bastardy; body; of death; bullion; clairvoyance; dancing; desynonymization; dichotomy; equality; etymology; flatting machine; genius; grammar; heterozetesis; hieroglyphs; hylozoism; idealism; imagination; kathos; laughing gas; liturgy; madness; mathematics; millennium; oneiromancy; oneiroscopy; opium; paneidolon; Books and reading; Marginalia; LITERARY CRITICISM / European / English; Irish; Scottish; Welsh